How does intelligent technology investment affect employment compensation and firm value in Chinese financial institutions?. Issue 4 (25th January 2022) - Lai, Zhoujing; Luo, Hang (Robin)
Abstract : Purpose: The authors intend to expand the literature on the relationship between intelligent technology and human resources in operating cost, and firm value of financial institutions in emerging markets by integrating the influence of intelligent technology and contribute to a growing body of literature on the determinants of firm value. Design/methodology/approach: This paper empirically investigates the impact of intelligent technology investment on employment compensation and firm value using a sample of 86 listed financial institutions in China from 2010 to 2019. Findings: This paper reports robust evidence that an increase in intelligent technology investment has a significantly negative effect on employment compensation in financial institutions. In addition, this inhibitory effect is persistent. The increase in intelligent investment has a significant two-year lag effect on firm value, which is positive and sustained. This indicates that intelligent technology investment has a short-term "useless" effect but brings long-term "gains" for Chinese financial institutions. Originality/value: These findings may shed light on the decision-making processes of financial institutions, which helps practitioners better understand that firms need to reasonably deal with the subsequent cost of growth caused by intelligent technology input. Alternatively, they may wish to select the appropriate accounting method of depreciation or amortization to smooth its impact.